The Influence of Innovation on Entrepreneurial Characteristics, on Shariah-Based Business Performance (Study of UKM Laundry registered with the Makassar City Cooperatives and UKM Service) - Amiruddin K; Ilham Gani (International Journal on Advanced Science, Education, and Religion, 2022)
This study aims to analyze the influence of entrepreneurial innovation characteristics on the performance of sharia-based businesses in laundry SMEs registered with the Makassar City Cooperatives and SMEs Service. The research approach uses a quantitative method with data collection techniques through questionnaires distributed to owners and managers of sharia-based laundry SMEs. The independent variables in this study are the characteristics of entrepreneurial innovation, which include creativity, courage to take risks, and the ability to see opportunities. Meanwhile, the dependent variable is business performance as measured by the level of profitability, customer satisfaction, and compliance with sharia principles. The results of the study indicate that the characteristics of entrepreneurial innovation have a positive and significant effect on the performance of sharia-based businesses. Creativity and the ability to see opportunities are the dominant factors that drive increased performance, while the courage to take risks has a more moderate effect. These findings emphasize the importance of innovation in the management of sharia-based SMEs to support business sustainability while improving community welfare.